The rheological, mechanical and heavy metal leaching properties of cemented paste backfill under the influence of anionic polyacrylamide. (January 2022) - Chen, Qiusong; Tao, Yunbo; Zhang, Qinli; Qi, Chongchong
Abstract: Anionic polyacrylamide (APAM) has widely been employed in backfill mining to accelerate the sedimentation of fine tailings particles and increase the concentration of tailings slurry. However, APAM inevitably remains in thickened tailings, leading to a nonnegligible influence on the rheological, mechanical, and heavy metal leaching properties of tailings-based cemented paste backfill (CPB). In an effort to solve these issues, the influences of APAM on CPB properties were examined in the present study. Experimental tests such as rheology, uniaxial compressive strength (UCS), toxicity leaching, and microscopy were conducted. The results showed that the presence of APAM first significantly increased the yield stress and viscosity of CPB slurry. APAM slightly improved the early UCS of CPB curing for 7 days but hindered the UCS development of samples cured for 28 days. Moreover, the presence of APAM restrained the hydration reaction, reduced the amounts of hydrated products, increased pore size, and loosed the microstructure of the test samples. Finally, the addition of APAM effectively reduced the leaching of Ag and As, while incremented that of Cu and slightly affected the leaching of Ba. In sum, these findings look promising for the safe production and environmental protection of the mining industry. Graphical abstract: Image 1 Highlights: APAM increased the yield stress and viscosity of CPB slurry. APAM hindered the UCS development of 28-day samples. APAM effectively reduced the leaching of Ag and As, while increased that of Cu and slightly affected the leaching of Ba.